KHULU’; PENYEIMBANG OTORITAS (INISIASI) CERAI DALAM SURAH AL-BAQARAH AYAT 229 - Aldin, Alfattiah; Izwany, Bonita (Sekolah Tinggi Ilmu Syariah Al-Hilal Sigli Aceh- Indonesia, 2024)
The life of a husband and wife in a household can only be upright if there is calm, affection, good association and each party carries out their obligations properly. But sometimes it happens that the husband hates his wife or the wife hates her husband. This means that if the marriage relationship is continued, harm will occur. So that at a time like this, Islam allows the dissolution of marriage as the last step in efforts to continue the household. And if hatred is on the part of the husband, then divorce is in his hand, which is one of his rights, but if hatred is on the part of the wife, then Islam allows her to redeem herself in the khulu way, namely returning the dowry to her husband to end the bond as husband and wife. In terms of the form of divorce that occurs as a result of khulu', several scholars differ in opinion. The first opinion, one of the narrations from Imam Ahmad says that khulu' is fasakh while the opinion of other scholars says that khulu' is divorce so this difference of opinion brings legal consequences how many times it is permissible to do khulu'. Based on this, the author wants to try to analyze the opinion of Ibn Hanbal who said that khulu' is fasakh. The results of the author's analysis show that divorce by way of khulu' takes the form of talak because this is in accordance with the statement of Surah Al-Baqarah verse 229 which says that khulu' cannot be referred to except with a new marriage, besides that Ibn Hanbal's opinion about khulu' as fasakh is not in accordance with the KHI where the KHI is the guideline for judges at the Religious Courts in resolving marital or divorce issues, and this is in accordance with articles 161 and 155 of the KHI.